Deep Fungal Infections Among General Hospital Inpatients in Southwestern China: A 5-Year Retrospective Study - Shu-Ran Wen; Zheng-Hui Yang; Tian-Xiang Dong; Yu-Ye Li; Yu-Ye Li; Ying-Kui Cao; Yi-Qun Kuang; Yi-Qun Kuang; Hong-Bin Li (Frontiers Media S.A., 2022)
BackgroundDeep fungal infection is a type of life-threatening opportunistic infection. Its incidence has been increasing in recent years. This infection can affect the prognosis of patients, prolong hospital stays and raise costs for patients and their families.ObjectiveWe aimed to understand the current situation of deep fungal infections in the First Affiliated Hospital of Kunming Medical University and to provide a basis for the clinical diagnosis and treatment of deep fungal infections.MethodsThis was a retrospective analysis of 528,743 cases in the hospital from 2015 to 2019, including the epidemiological characteristics, treatment and prognosis of deep fungal infections.ResultsA total of 274 cases (0.05%) with deep fungal infections were identified, accounting for 0.05% of the total number of hospitalizations. The incidence of deep fungal infections in the hospital showed an increasing trend from 2015 to 2019. The most commonly infected site was the respiratory tract (93.07%). Among patients with deep fungal infections, 266 specimens were positive for fungal culture, by which 161 cultured Candida albicans (C. albicans), accounting for 60.53%, the main pathogen causing deep fungal infection. From 2015 to 2019, the percentage of C. albicans cases showed a downward trend, while that of non-C. albicans showed an opposite trend. Antibiotics were the most common predisposing factor for deep fungal infections (97.45%). Among the underlying diseases of patients with deep fungal infections, infectious diseases (59.49%) were the most common. Those with underlying diseases such as renal insufficiency and neurological diseases had a worse prognosis. Indwelling catheters, nervous system disease and tumors were risk factors for a poor prognosis.ConclusionsWe report for the first time the epidemiological data of deep fungal infections in a general hospital in southwestern China from 2015 to 2019. In the past 5 years, the number of patients with deep fungal infections in the First Affiliated Hospital of Kunming Medical University has been increasing. Although the clinical data are limited, these results can provide references for the diagnosis and treatment of deep fungal infections.